Analisis Dampak Negatif Social Media dan E-Commerce (Social Commerce) Pada Usaha Mikro Kecil Menengah - Fitri, Mulyana; Sirait, Frida Yanti; Batubara, Maryam (Movere Journal, 2024)
Social Ecommerce, which has become a global phenomenon, combines elements of social media and e-commerce to provide a platform for sellers to market and sell their products online. Research uses library research (Library Research). Research results include the negative impact of social media on MSMEs, namely that social media platforms consume a lot of energy and time to manage accounts, mistakes in advertising, traps for wasting work time and diverting attention in other directions that are far from the desired goals. obtained some inaccurate data about the company's performance, due to dealing with hidden people. MSMEs have a big impact on e-commerce, what e-commerce faces is customers' fear of electronic attacks and information piracy, and weak levels of advertising. One of the main impacts that may arise is the possibility of a decrease in turnover, so the government decided to close TikTokshop only to be used as promotional media, not as a marketplace.